Penerapan Pursed LIP Breathing terhadap Penurunan Sesak Napas pada Pasien Penyakit PPOK di Ruang HCU - Mudrikah AZ; Liliy Wahyu Romadhon; Citra Setyo Dwi Andini (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation and commonly associated with dyspnea. Uncontrolled dyspnea may decrease patients' functional capacity and quality of life. One of the non-pharmacological interventions that can be applied to reduce dyspnea is the Pursed Lip Breathing (PLB) technique. This Final Nursing Scientific Project aimed to describe the application of Pursed Lip Breathing in reducing dyspnea among COPD patients at Gunung Jati Regional Hospital, Cirebon. This study used a descriptive case study approach through the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. The Pursed Lip Breathing technique was implemented according to the standard operating procedure in COPD patients with an ineffective breathing pattern nursing diagnosis. The results showed an improvement in respiratory status, indicated by decreased dyspnea, reduced respiratory rate, increased oxygen saturation, and decreased use of accessory respiratory muscles. The patient also appeared more comfortable and was better able to control breathing patterns following the intervention. In conclusion, the Pursed Lip Breathing technique is an effective non-pharmacological nursing intervention for reducing dyspnea in patients with COPD.